Towards the Transformation of Whiteness, the White Centered National Narrative, Racial Categories and the Self in Maxine Hong Kingston’s The Fifth Book of Peace - Klara Szmańko (European Journal of American Studies)
The Fifth Book of Peace (2003) marks the evolution of Maxine Hong Kingston’s vision of whiteness and the very definition of racial categories in her works. In The Fifth Book of Peace, Kingston assumes a much more transnational perspective, reflecting to a greater extent on the enmeshment of whiteness in imperialist and colonizing practices beyond the perimeter of the mainland United States and the territory of the United States as a whole. While in The Fifth Book of Peace Kingston notes the implication of whiteness in colonization and imperialism, she also to a greater extent stresses its potential for transformation. This potential was hinted at in The Woman Warrior, but it is much more explicitly elaborated on only in The Fifth Book of Peace. All of Kingston’s works are written in the spirit of transformational identity politics and intersectionality. In all of her works, Kingston notices the intersection of diverse types of oppression, going beyond exposing the stripes of exploitation that immediately affect the major characters of her works. Yet it is in The Fifth Book of Peace that she underscores the need for cooperation between individuals affected by diverse types of trauma stemming from different kinds of oppression. It is also in The Fifth Book of Peace that Kingston envisions the possibility of white Americans cooperating with people of other races and nationalities on behalf of peace rather than in the name of war, expansion and colonialism symbolized in the narrative by the wars in Vietnam, Iraq and the colonization of Hawaii.